DEV-13. PRELIMINARY RESULTS OF A BRAZILIAN CENTRAL NERVOUS SYSTEM GERM CELL TUMOR CONSORTIUM PROTOCOL. Issue 2 (22nd June 2018) - Cappellano, Andrea M; Finlay, Jonathan; Mançano, Bruna; Barbosa, Daniela; Cavalheiro, Sergio; Dastoli, Patricia A; Silva, Frederico A; Aguiar, Simone S; Valera, Elvis; da Silva, Nasjla Saba
Abstract: INTRODUCTION: Primary central nervous system (CNS) germ cell tumors (GCT) account for 2–3% of brain tumors in children/adolescents in Western hemisphere, being classified as germinomas and non-germinomatous GCT (NGGCT). Our objective is to report the results of a Brazilian CNSGCT consortium protocol. MATERIALS/METHODS: Since 2013, 28 patients with histologic and/or tumor marker (TM) diagnosis of germinoma with/without HCGβ levels ≤200mIU/ml (n=21) and NGGCT (n=7), received four/six cycles of carboplatin/etoposide/cyclophosphamide, followed by 18Gy ventricular field irradiation (VFI) and primary site(s) boost. Autologous bone marrow transplant (ABMT) was conducted for NGGCT low responders. RESULTS: Median age-13, 5 years, 21 males. Diagnosis was made by TM (n=5), surgery (n=14), both (n=7). Two bifocal cases, TM(-) were treated as germinoma. Primary tumor location was pineal(n=14), suprasellar(n=7), bifocal (n=7). Nine had ventricular/spinal spread. Second-look surgery occurred in five patients. For the germinoma group, 18 patients achieved complete response (CR) after chemotherapy, the remaining 4 showed residual teratoma/scar. The NGGCT patients (n=7) showed partial responses(n=5), three with TM(-) and two CR after 4/6 cycles. Two patients were submitted to ABMT. Radiotherapy was performed as described except in two. No recurrences to date. One patient died of endocrinologic complications. Toxicity was mostly grade ¾ neutropenia/thrombocytopenia (NGGCT) following cyclophosphamide and in all patients for at least one cycle following carboplatin. At a median follow-up of 29, 6 months, event-free and overall survival was 96, 4%. CONCLUSION: Dose reduction of VFI to 18Gy seems to preserve efficacy. Further follow-up is warranted to better assess treatment efficacy especially among the slow responder patients.